KESENIAN BELUK PADA MASYARAKAT KAMPUNG KADU HEULANG DESA CISEREH KABUPATEN PANDEGLANG-BANTEN - Wahyudin, Asep; Suhaya, Suhaya; Permana, Rian (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2023)
This study aims to find out the general description and function of Beluk art in Kampung Kadu Heulang, Cisereh Village, Cisata sub-district, Pandeglang-Banten Regency, which is motivated by a lack of broad understanding of the function of Beluk in society. This study uses a qualitative research method with an ethnographic research design to describe and interpret culture, social groups or systems. The data analysis technique uses interactive models, data presentation, and conclusions drawing/verifying. The results of this study are that the form of presentation of the Beluk art in Kampung Kadu Heulang has its own uniqueness both before and after the performance. As for the initial function of Beluk art, namely as a means of communication by farmers, over time, Beluk art was used as a means of religion, entertainment, and social, so it can be concluded that Beluk Art in Kadu Heulang Village, Cisereh Village, Cisata District, Pandeglang Regency is still being preserved and maintained properly. both from the first generation to the fourth generation.